Mesenchymal Stem Cells Secretome and Osteoarthritis: A State of The Art - Soetjahjo, Bintang; Utomo, Dwikora Novembri (Indonesian Hip and Knee Society (IHKS), 2022)
No agreed cure or procedure can prevent the damage caused by OA. Current treatments such as physiotherapy, anti-inflammatory drugs, and viscous supplements are symptomatic and are aimed solely at pain relief. Mesenchymal stem cells, on the other hand, refer to a population of cells with immunomodulatory and homing properties. Recent studies have shown that stem cells produce secretomes with tissue regeneration, immunomodulation, anti-inflammatory, and anti-apoptotic capacities.Secretomes in conditioned media produced by mesenchymal stem cells can stimulate the repair of cartilage defects. There are many evidence from many studies both in vitro and in vivo which provide potential results. The improvement can be seen from the morphology, in the form of thickening of the cartilage, an increase in the number of chondrocyte cells, regular joint surfaces, and histologically it can be seen that there is an improvement in the joint cartilage matrix. Likewise, histological studies using immunohistochemistry also showed an increase in the expression of TGF-β, SOX-9, aggrecan, and type II collagen which is a pathway for the formation of hyaline cartilage repair. Not only improvement, other studies have also shown that the secretome can provide a protective effect on joint cartilage by increasing the expression of the COL2A1 gene which functions to form collagen matrix components and reduces apoptosis in chondrocyte cells.Secretomes produced by mesenchymal stem cells can stimulate the repair of cartilage damage, anti-inflammatory, immunomodulator, angiogenesis, and anti-apoptotic abilities from their cytokines and extra vesicles contains miRNA. MSCs secretomes are more stable and provide simpler manufacturing than MSCs themselves.